2010
DOI: 10.1177/0363546509353406
|View full text |Cite
|
Sign up to set email alerts
|

Single-Tunnel Double-Bundle Anterior Cruciate Ligament Reconstruction with Anatomical Placement of Hamstring Tendon Graft

Abstract: Background Anatomical reconstruction techniques that can restore normal joint kinematics without increasing surgical complications could potentially improve clinical outcomes and help manage anterior cruciate ligament injuries more efficiently. Hypothesis Single-tunnel double-bundle anterior cruciate ligament reconstruction with anatomical placement of hamstring tendon graft can more closely restore normal knee anterior-posterior, medial-lateral, and internal-external kinematics than can conventional single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 40 publications
(69 reference statements)
0
37
0
Order By: Relevance
“…Much of this work has evaluated and improved the efficaciousness of surgical methods and graft material selections used in ACL reconstructions with respect to native ACL biomechanics [12,15,19,20,28,35,43,49,51,[56][57][58]. These simulations have also gathered data on the mechanical contributions of the intact ACL in response to Lachman's and pivot shift tests [15,19,20,28,35,43,49,51,[56][57][58], gait cycles [23,39], and landing impact forces [32,40,41,46,52,53]. The accrued data have advanced the knowledge of ACL function and provided a baseline of comparison by which to evaluate the effectiveness of ACL injury treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Much of this work has evaluated and improved the efficaciousness of surgical methods and graft material selections used in ACL reconstructions with respect to native ACL biomechanics [12,15,19,20,28,35,43,49,51,[56][57][58]. These simulations have also gathered data on the mechanical contributions of the intact ACL in response to Lachman's and pivot shift tests [15,19,20,28,35,43,49,51,[56][57][58], gait cycles [23,39], and landing impact forces [32,40,41,46,52,53]. The accrued data have advanced the knowledge of ACL function and provided a baseline of comparison by which to evaluate the effectiveness of ACL injury treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, return to pre-injury level, overall IKDC, pivot shift and anterior laxities after single bundle and double bundle ACL reconstructions demonstrated that both techniques result in similar antero-posterior knee joint laxity at time 0. Therefore, no conclusive evidence on the superiority of one reconstruction technique over the other in terms of rotation laxity could be obtained 17 .…”
Section: Antero-medial Portal Vs Transtibial Femoral Tunnel Drillingmentioning
confidence: 99%
“…In the case of the STG autograft, a further delineation can be drawn with the potential for either a single or double bundle method (Branch, Siebold, Freedberg, & Jacobs, 2011;Chalmers et al, 2013;Gadikota et al, 2010;Jarvela, 2007;Lewis et al, 2008;van Eck et al, 2010). Although the proposition of a double bundle method has been around since the 1930's, the technique has become more popular in recent years with advancements in surgical methodology and the suggestion that it more closely resembles the native ACL; hence improving patient outcomes (Chalmers et al, 2013;Gadikota et al, 2010;Karlsson et al, 2011;Park et al, 2010;Schindler, 2012;van Eck et al, 2010).…”
Section: Graft Selectionmentioning
confidence: 99%
“…Although the proposition of a double bundle method has been around since the 1930's, the technique has become more popular in recent years with advancements in surgical methodology and the suggestion that it more closely resembles the native ACL; hence improving patient outcomes (Chalmers et al, 2013;Gadikota et al, 2010;Karlsson et al, 2011;Park et al, 2010;Schindler, 2012;van Eck et al, 2010).…”
Section: Graft Selectionmentioning
confidence: 99%
See 1 more Smart Citation